Gambaran Tingkat Kepuasan Mahasiswa S1 Keperawatan Terhadap Pelaksanaan Osca Di Universitas Muhammadiyah Surakarta - Hati, Harti Cahya; , Enita Dewi, S.Kep., Ns., MN (2017)
Abstract Introduction OSCE/OSCA is a method of evaluation used to assess the students' clinical skill, either psychomotor skill, knowledge, or attitude which are simultaneously assessed at the same time. In the implementation of OSCA, there are several equipment which are provided before the examination, such as room or station, examiner, assessment checklist, standardized patient, as well as the equipment and materials that will be used by the students. OSCE/OSCA is important for the students and has superiority that OSCE has positive impacts, one of the impacts is making the students more prepared before practicing in the hospital. Purpose this research aims to explain about the students' satisfaction level of nursing undergraduate in having the examination of OSCA. The method of research used is a descriptive quantitative research. The sample used in this research is the nursing students of the 3rd semester of Muhammadiyah University of Surakarta as many as 105 respondents. The technique of sampling used is purposive sampling. The instrument used to obtain the data is questionnaire about the the students' satisfaction level in OSCA. The analysis used is univariate. The results of the research revealed that from the five researched categories, in the first category, the students' satisfaction on the facilitator of OSCA, the biggest distribution is satisfying enough as much as 61 (58.1%); second, the students' satisfaction on the assessment system of OSCA, the biggest distribution is satisfying enough as much as 46 (43.8%); third, from the students' satisfaction on themselves in the process of OSCA, the biggest distribution is satisfying enough as much as 59 (56.2%), fourth, from the students' satisfaction on the facilities of OSCA, the biggest distribution is satisfying enough as much as 51 (48.5%), and fifth, from the students' satisfaction on the process of OSCA, the biggest distribution is satisfying enough as much as 71 (67.6%). Conclusion from this research, from the five categories which are researched, the most distribution is satisfying enough from all respondents. Keywords: OSCA (objective structured clinical assessment), satisfaction, students.